An Examination of Curriculum Planning in Nigeria’s Teacher Education: Challenges and Way Forward - Ali, Umar Magaji; Maigari, Halima; Umar, Nafisat Saleh; Saleh , Badamasi Abdullahi (Kashere Journal of Education, 2025)
This study examines the challenges facing curriculum planning in the Nigerian teacher education system and identifies strategies for improvement. The curriculum planning in Nigeria has been facing various challenges over the years, hindering its effectiveness and efficiency. The purpose of this study is to identify and analyse the barriers to effective curriculum planning in Nigeria. The study reveals that the curriculum planning process is plagued by inadequate resources, poor infrastructure and a lack of expertise in curriculum design and development. The paper is a review paper that depends on secondary data. The secondary data were collected from print and online publications. The paper identified poor funding, a shortage of curriculum planning experts, poor capacity development of curriculum experts and a lack of data on learners’ information. This has resulted in poor curriculum planning in Nigeria. Based on the findings, the paper recommends that government should increase the funding of education, employ more curriculum planning experts, ensure accurate data generation and provide constant training and retraining programmes for the planners